PENGARUH CURRENT RATIO TERHADAP NILAI PERUSAHAAN DENGAN RETURN ON ASSETS SEBAGAI VARIABEL MEDIASI PADA PT KALBE FARMA Tbk TAHUN 2018-2025 - hana widyana; Dewi Salsa Billa Puspita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of Current Ratio (CR) on firm value as measured by Price to Book Value (PBV), with Return on Assets (ROA) acting as a mediating variable at PT Kalbe Farma Tbk during the 2018–2025 period. The research employed a quantitative approach with a causal associative design. The data used were secondary data obtained from the quarterly financial statements of PT Kalbe Farma Tbk. Purposive sampling was applied, resulting in 32 observations. Data analysis was conducted using SPSS through descriptive statistical analysis, classical assumption tests, regression analysis, and path analysis. The results indicate that Current Ratio has no significant effect on Return on Assets, with a significance value of 0.094 (>0.05). Current Ratio also has no significant effect on Price to Book Value, with a significance value of 0.684 (>0.05). Furthermore, Return on Assets has no significant effect on Price to Book Value, with a significance value of 0.327 (>0.05). The path analysis results reveal that Return on Assets is unable to mediate the relationship between Current Ratio and Price to Book Value because the indirect effect is smaller than the direct effect and the relationships among variables are statistically insignificant. Therefore, liquidity and profitability were not the primary factors influencing the firm value of PT Kalbe Farma Tbk during the research period.